The Cultural Property Claim within the Same-Sex Marriage Controversy - Poirier, Marc R. (Columbia Journal of Gender and Law, 2008)
Partisans in the contemporary controversy over same-sex marriage and marriage equality often use the rhetoric of “access” and “exclusion” to frame their positions. These terms are also used to stake out positions on how to resolve conflicts over congestible natural resources. This Article takes the terms at face value and asks whether and how the marriage equality/same-sex marriage controversy might usefully be described in terms of a controversy over a contested and potentially congestible shared resource. “Access” and “exclusion” are property language, after all. This Article will argue that the traditionalist’ claim that same-sex couples should be excluded from marriage is the same kind of claim as is often made by Native American, indigenous, and other culturally- subordinated groups to certain cultural resources-a right to exclude others in order to protect sacred objects, places, and rituals, so as to preserve and perpetuate group identity over time. This description may help progressives gain a new, and perhaps better, understanding of the sense often expressed by traditionalists of the harm they believe would accrue by allowing same- sex couples access to the institution of marriage.2 The Article explores the details of the traditionalist position understood as a cultural property claim and then sketches out a number of progressive responses to the traditionalists’ cultural property claim.